Anti-atherosclerosis and cardio-protective effects of the Angong Niuhuang Pill on a high fat and vitamin D3 induced rodent model of atherosclerosis. (4th January 2017) - Fu, Wen-Juan; Lei, Ting; Yin, Zhen; Pan, Jian-Hao; Chai, Yu-Shuang; Xu, Xiao-Yun; Yan, Yi-Xi; Wang, Zhi-Hua; Ke, Jian; Wu, Gang; Xu, Ren-He; Paranjpe, Manish; et al.
Abstract: Ethnopharmacological relevance: The Angong Niuhuang Pill (ANP) is a well known Chinese traditional therapeutic for the treatment for diseases affecting the Central Nervous System (CNS). Components of the ANP formulation, including Bovis Calculus Sativus, Pulvis Bubali Comus Concentratus, Moschus, Margarita, Cinnabaris, Realgar, Coptidis Rhizoma, Scutellariae Radix, Gardeniae Fructus, Curcumae Radix, and Bomeolum Syntheticum, have been used for the treatment of stroke, encephalitis and emergency meningitis across Asia, especially in China for hundreds of years. Objective: The goal of this study was to investigate the anti-atherosclerosis and cardio-protective effects of ANP administration using a rodent model of atherosclerosis induced by a high fat and vitamin D3 . Methods: Specific Pathogen-Free (SPF) 78 male SD rats were randomly divided into a control group and 5 atherosclerotic model groups. The atherosclerotic groups were divided to receive either Simvastatin (SVTT, 0.005 g/kg), Low-dose ANP (0.125 g/kg), Medium-dose ANP (0.25 g/kg), and High-dose ANP (0.5 g/kg). Following adaptive feeding for one week, atherosclerosis was induced and the atherosclerosis model was established. Experimental drugs (either simvastatin or ANP) or normal saline were administered intragastrically once daily for 9 weeks starting from the 8th week. A carotid artery ultrasound was performed at the 17th week to determine whether atherosclerosis had been induced. After the atherosclerosis model was successfully established, platelet aggregation rates, serum biochemical indices, apoptosis-related Bcl-2, Bax proteins levels in the heart were assayed. Pathological and histological analysis was completed using artery tissue from different experimental different groups to assess the effects of ANP. Results: ANP signiﬁcantly decreased aortic membrane thickness, the maximum platelet aggregation rates, and the ratio of low density lipoprotein cholesterol (LDL) to high density lipoprotein cholesterol (HDL). In addition, ANP signiﬁcantly reduced serum contents of total cholesterol, low density lipoprotein, malondialdehyde, troponin I, high-sensitivity C-reactive protein, and lactate dehydrogenase. ANP markedly improved abnormal pathological conditions of the aorta and heart, and helped to prevent myocardial apoptosis. Conclusions: We have demonstrated that ANP has robust ant-atherosclerosis and cardio-protective effects on a high-fat and vitamin D3 – induced rodent model of atherosclerosis due to its antiplatelet aggregation, lipid regulatory, antioxidant, anti-inflammatory and anti-apoptotic properties. Graphical abstract: